2009
DOI: 10.2478/v10001-009-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes of low-dose ionizing radiation exposure among medical workers: a cohort study of the Canadian national dose registry of radiation workers

Abstract: Background: Medical workers can be exposed to low-dose ionizing radiation from various sources. The potential cancer risks associated with ionizing radiation exposure have been derived from cohort studies of Japanese atomic bomb survivors who had experienced acute, high-level exposure. Since such extrapolations are subject to uncertainty, direct information is needed on the risk associated with chronic low-dose occupational exposure to ionizing radiation. Objectives: To determine the occupational doses of ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 20 publications
(39 reference statements)
4
45
0
3
Order By: Relevance
“…Thus, it is known that exposure to ionizing radiation, especially in childhood, increases the risk of developing thyroid cancer (Silverman, 1984;IARC, 2001;Zielinski et al, 2009;Furukawa et al, 2013) However, it is still not clear why thyroid cancer is markedly predominant in females. Previous observational studies on the reproductive system have produced conflicting results (Akslen et al, 1992;Pham et al, 2009;Horn-Ross et al, 2011;Kabat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is known that exposure to ionizing radiation, especially in childhood, increases the risk of developing thyroid cancer (Silverman, 1984;IARC, 2001;Zielinski et al, 2009;Furukawa et al, 2013) However, it is still not clear why thyroid cancer is markedly predominant in females. Previous observational studies on the reproductive system have produced conflicting results (Akslen et al, 1992;Pham et al, 2009;Horn-Ross et al, 2011;Kabat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic and therapeutic applications, such as X rays and other medical devices, are an important source of IR and pose a significant risk of occupation-related exposure to IR. This poses a huge problem with regard to health of the exposed occupational group and for hospitals in managing occupational health risks (2,6,7) . Considering the serious radiological effects of IR on human health, the health risk to Chinese workers in different occupations, particularly in a healthcare setting, is important to understand (2) .…”
Section: Introductionmentioning
confidence: 99%
“…There was also evidence of an increased risk of lung and thyroid tumors in radiological technologists who were frequently exposed to radiation as they assisted patients during x-rays, 85À86 and lung cancer in those who allowed others to practice x-rays on them. 86 Studies in various countries have also observed increased risks of leukemia, breast cancer, and skin cancer, 87 as well as thyroid cancer 88 in female workers exposed to ionizing radiation.…”
Section: Health Carementioning
confidence: 97%
“…However, few studies of thyroid cancer and occupational risk factors among women have been conducted. Increased risk of thyroid cancer has been observed in women with exposure to ionizing radiation, 88 such as x-rays, 72,80 including health care workers, 70À71 radiological technologists, 85 dentists, and dental assistants. 72 Increased risk has also been observed in women employed as dry cleaners, 25 tailors, shoemakers and shoe cutters, 70,72 shop managers, 70 teachers, 72 warehouse workers, 72 the textile industry, 154 electric installation work, 70 and in women exposed to silica, 296 video display terminals, 72 and solvents in the shoe and leather industry.…”
Section: Breastmentioning
confidence: 99%